2021
DOI: 10.3390/metabo11050263
|View full text |Cite
|
Sign up to set email alerts
|

Zero Echo Time 17O-MRI Reveals Decreased Cerebral Metabolic Rate of Oxygen Consumption in a Murine Model of Amyloidosis

Abstract: The cerebral metabolic rate of oxygen consumption (CMRO2) is a key metric to investigate the mechanisms involved in neurodegeneration in animal models and evaluate potential new therapies. CMRO2 can be measured by direct 17O magnetic resonance imaging (17O-MRI) of H217O signal changes during inhalation of 17O-labeled oxygen gas. In this study, we built a simple gas distribution system and used 3D zero echo time (ZTE-)MRI at 11.7 T to measure CMRO2 in the APPswe/PS1dE9 mouse model of amyloidosis. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…17 O can be administered in the form of water via various routes depending on the targeted water dynamics, including intravascular, inhalation, and more recently, intrathecal, ophthalmic, intra-articular, and ear drop routes. Of note, although it is outside the scope of this review that focuses on 17 O-labeled water, it should be mentioned that 17 O can also be administered as a gas (O 2 ), and the cerebral metabolic rate of oxygen can be measured by detecting 17 O-labeled water produced in vivo by inhaling 17 O-labeled oxygen gas 4–7,9–22,31–35 . Furthermore, 17 O can be labeled on compounds such as glucose, 36,37 and 17 O-labeled metabolic water resulting from 17 O-labeled compounds can be detected.…”
Section: Characteristics Of 17o-labeled Water Tracer and Its Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…17 O can be administered in the form of water via various routes depending on the targeted water dynamics, including intravascular, inhalation, and more recently, intrathecal, ophthalmic, intra-articular, and ear drop routes. Of note, although it is outside the scope of this review that focuses on 17 O-labeled water, it should be mentioned that 17 O can also be administered as a gas (O 2 ), and the cerebral metabolic rate of oxygen can be measured by detecting 17 O-labeled water produced in vivo by inhaling 17 O-labeled oxygen gas 4–7,9–22,31–35 . Furthermore, 17 O can be labeled on compounds such as glucose, 36,37 and 17 O-labeled metabolic water resulting from 17 O-labeled compounds can be detected.…”
Section: Characteristics Of 17o-labeled Water Tracer and Its Imagingmentioning
confidence: 99%
“…In contrast to MRI macrotracers such as Gd contrast agent, which distribute within specific water compartments, 17 O water serves as a tracer, allowing its distribution in various water compartments. Although the biomedical application of MRI using stable 17 O isotopes has been explored, primarily focusing on tissue oxygen metabolism using 17 O-labeled gases since the 1990s, [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] a growing body of research has emerged on MR water imaging using 17 O-labeled water in vivo since approximately 2010. [23][24][25][26][27][28][29][30] In this review, we summarized the fundamentals and diverse applications of MR-WTI (MR water tracer imaging) using 17 O-labeled water.…”
mentioning
confidence: 99%
“…A 17 O MRI approach for studying the cerebral oxygen metabolism was developed for rats about two decades ago ( Zhu et al, 2002 ). Since then, several pathologies have been studied in mice using 17 O MRI, such as amyloidosis ( Baligand et al, 2021 ) and Huntington’s disease ( Lou et al, 2016 ). The safe and feasible application of indirect ( Harada et al, 2022 ) and direct 17 O MRI ( Fiat et al, 1993 , 2004 ), and 17 O MR spectroscopy ( Zhu et al, 2005 ) to humans has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%